PENGARUH KUALITAS DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PRODUK SEPATU CONVERSE: (Studi pada Mahasiswa Kota Bogor yang menggunakan Produk Sepatu Converse) - Kamila; Hartono, Budi (Transpublika Publisher, 2022)
This study aims to determine the effect of product quality and brand image on the decision to purchase Converse brand shoes for students in the city of Bogor. This type of research is quantitative research. Data collection is done by distributing online questionnaires using Google Forms. The population used in this study were students in the city of Bogor. While the sampling technique using purposive sampling with the number of samples to be taken as many as 50 respondents who have made a purchase of Converse shoe products. From the results of this study, the variable of product quality has a positive and significant effect on purchasing decisions for Converse brand shoes for students in the city of Bogor. While the Brand Image variable has a positive effect but does not have a significant influence on the decision to buy Converse shoes for students in the city of Bogor so that companies are required to continue to build a positive Converse Brand Image such as promotions and provide maximum service in branding in order to get consumer appeal.